De-demonizing the ‘monstrous’ drug addict: a qualitative look at social reintegration through rehabilitation and employment - Lutman, Brandon (Critical criminology, 2015)
Few studies explore how employers perceive the experience of hiring recovering substance abusers. Qualitative, semi-structured interviews were conducted with employers who hire clients from a residential drug treatment facility for adult males in a capital city in the southeastern United States as well as several administrators that work at this facility. The emergent themes uncovered through these interviews shed light on the opinions of those who refuse to abandon a population of individuals who have been neglected by so many others. The research participant insights shed light on the fact that when overcoming drug addiction and abuse, getting sober is only half the battle. These individuals are then left to fight against the labels and stigmatization cast upon them by society. Information gleaned from these interviews may offer employers who may consider hiring ex-offenders, insights into potential benefits and problems they may encounter in working with this population. The findings of this study emphasize the damning effects of labeling on the social reintegration of those desperate for a second chance at being productive members of society.